2010
DOI: 10.3109/08958370903456645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a nose-only inhalation exposure system for hydrocarbon mixtures and jet fuels

Abstract: A directed-flow nose-only inhalation exposure system was constructed to support development of physiologically based pharmacokinetic (PBPK) models for complex hydrocarbon mixtures, such as jet fuels. Due to the complex nature of the aerosol and vapor-phase hydrocarbon exposures, care was taken to investigate the chamber hydrocarbon stability, vapor and aerosol droplet compositions, and droplet size distribution. Two-generation systems for aerosolizing fuel and hydrocarbons were compared and characterized for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…For the jet fuels, the GC oven Percent aerosol and percent vapor were determined based on the mean of aerosol/vapor data collected with TDS charcoal tubes (see Methods). Aerosol size characteristics for the current study were determined using a cascade impactor, via the method and conditions reported by Martin et al (2010). *The percent of total hydrocarbon concentration, minus the marker chemical concentrations from within the lumps, is listed for each lump.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the jet fuels, the GC oven Percent aerosol and percent vapor were determined based on the mean of aerosol/vapor data collected with TDS charcoal tubes (see Methods). Aerosol size characteristics for the current study were determined using a cascade impactor, via the method and conditions reported by Martin et al (2010). *The percent of total hydrocarbon concentration, minus the marker chemical concentrations from within the lumps, is listed for each lump.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrocarbon compositions of vaporized JP-8 and aerosolized JP-8, S-8, and the blended fuel constituents have been reported in previous work Martin et al, 2010;Tremblay et al, 2010b). Six representative hydrocarbons were selected as marker chemicals for JP-8 (n-octane, n-decane, n-tetradecane, toluene, m-xylene, and ethylbenzene) and 3 hydrocarbon markers for S-8 (n-octane, n-decane, and n-tetradecane).…”
Section: Pbpk Fuel Modelmentioning
confidence: 99%
See 3 more Smart Citations